GANDHI AMBEDKAR DEBATE - T, Suchithra; K S, Girija (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The present paper intends to explore the divergent perspectives and paths of Mohandas Karamachand Gandhi and Dr B R Ambedkar on different socio-political issues of Indian Society. Before Independence, Outsiders (Aliens, British People) ruled India. Gandhi was afraid of our own people ruling like outsiders (alienation of administration) after Independence. However, in the light of the present context Gandhi’s fear has come true. On the other side Dr. B R Ambedkar strongly believed in State power and a strong legal system. Catastrophically the dreams of Dr B R Ambedkar on social economic equality remains a myth. To understand the dynamics of two variant discourses of Gandhi and Dr B R Ambedkar and to follow both Gandhi and Ambedkar Principles are essential. Both ideas of Gandhi Ambedkar together bring a better order in India. People not only from the East but also from western world are inspired by Gandhian Principles of Truth and Non-Violence. The people of the world consider Ambedkar as an icon for Equality. Ideas of both Gandhi and Ambedkar could generate political consciousness among socially marginalized groups. Though both Gandhi and Ambedkar had different ideas and Concepts, and followed different paths both wanted to reform Indian society in general and Hindu Society in particular. Gandhi was influenced by Dr B R Ambedkar. At one point of time Gandhi wanted to fight for the cause of untouchables.